Tungsten and Titanium Oxide Thin Films Obtained by the Sol-Gel Process as Electrodes in Electrochromic Devices - Rizzuto, Carmen; Barberi, Riccardo C.; Castriota, Marco (Frontiers in Materials, 2022)
In this work, WO3 and TiO2 thin films have been obtained by sol-gel spin coating-method. The as-deposited samples were annealed at different annealing temperatures in the range between 100 °C and 500°C. Micro-Raman spectroscopy confirmed that WO3 thin films annealed at 100 °C and 300 °C are amorphous while the crystallization process occurred at 500 °C as established by the typical Raman modes of -WO3. Amorphous thin films of TiO2 have been obtained using annealing at 100 °C and 300 °C. The crystalline phase of the Anatase-TiO2 have been obtained after the thermal treatment conducted at 500 °C. Single electrodes have been used for assembling various electrochromic devices. The electrochemical properties of each device have been studied by Cyclic Voltammetry that confirmed the reversibility and the electrochromic behavior of the devices. The main technological properties, such as transmittance and coloration efficiency of the electrochromic devices have been studied by UV-Vis-NIR spectroscopy and they have been related to the annealing temperature to whom the used electrode was subjected. The UV-Vis-NIR analysis has confirmed that the best configurations of the electrochromic devices studied in this work can be obtained by using the WO3 thin films amorphous, that means annealed at 100°C and 300°C, and TiO2 thin films crystalline, that is annealed at 500°C. The higher CE values in the visible region (λ=550 nm) and in the near infrared region (λ=1020 nm) support the idea that such devices could be used in order to control the light flux but also the heat flux and therefore, for energy saving applications.